Enterovirus Infections Are Associated With the Development of Celiac Disease in a Birth Cohort Study - Oikarinen, Maarit; Puustinen, Leena; Lehtonen, Jussi; Hakola, Leena; Simell, Satu; Toppari, Jorma; Ilonen, Jorma; Veijola, Riitta; Virtanen, Suvi M.; Knip, Mikael; Hyöty, Heikki (Frontiers in Immunology, 2021)
Enterovirus and adenovirus infections have been linked to the development of celiac disease. We evaluated this association in children who developed biopsy-proven celiac disease during prospective observation starting from birth, and in control children matched for the calendar time of birth, sex and HLA-DQ genotype. Enterovirus and adenovirus infections were diagnosed by seroconversions in virus antibodies in longitudinally collected sera using EIA. Enterovirus infections were more frequent in case children before the appearance of celiac disease-associated tissue transglutaminase autoantibodies compared to the corresponding period in control children (OR 6.3, 95% CI 1.8-22.3; p=0.005). No difference was observed in the frequency of adenovirus infections. The findings suggest that enterovirus infections may contribute to the process leading to celiac disease.